The Methodology of Modern Macroeconomics and the Descriptive Approach to Discounting - Koen Vermeylen (Tinbergen Institute, 2013)
Critics of modern macroeconomics often raise concerns about unwarranted welfare conclusions and data mining. This paper illustrates these concerns with a thought experiment, based on the debate in environmental economics about the appropriate discount rate in climate change analyses: I set up an economy where a social evaluator wants to determine the optimal time path of emission levels, and seeks advice for this from an old-style neo-classical macroeconomist and a new neo-classical (modern) macroeconomist; I then describe how both economists analyze the economy, their policy advice, and their mistakes. I then use the insights from this thought experiment to point out some pitfalls of the modern macroeconomic methodology.
Keywords: B22; B41; E13; O44; Q52; Q54; 330; modern macroeconomics; methodology; descriptive; prescriptive; discount rate